2021
DOI: 10.1038/s41588-021-00955-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of LZTFL1 as a candidate effector gene at a COVID-19 risk locus

Abstract: The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) disease (COVID-19) pandemic has caused millions of deaths worldwide. Genome-wide association studies (GWAS) identified the 3p21.31 region as conferring a two-fold increased risk of respiratory failure. Here, using a combined multiomics and machine-learning approach, we identify the gain-of-function risk A allele of a single-nucleotide polymorphism (SNP), rs17713054G>A, as a probable causative variant. We show with chromosome conformation capture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
119
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(130 citation statements)
references
References 115 publications
8
119
1
2
Order By: Relevance
“…The strong expression of CEBPB in lung tissue supports the biological relevance of this new motif ( 64) and chromatin immunoprecipitation supported by sequencing (ChIP-seq) of CEBPB in lung broblast cells of IMR-90 and HeLa, A549 alveolar basal epithelial adenocarcinoma (65). Moreover, deepHaem predicted that rs17713054-A would resulted in induced binding of CEBPB in A549 cells and IMR-90 (29) . This study found that rs17713054is an active enhancer of LZTFL1 in lungs and associated with increased risk of COVID-19 and is not in an active enhancer in immune cells, where CCR9 is expressed.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…The strong expression of CEBPB in lung tissue supports the biological relevance of this new motif ( 64) and chromatin immunoprecipitation supported by sequencing (ChIP-seq) of CEBPB in lung broblast cells of IMR-90 and HeLa, A549 alveolar basal epithelial adenocarcinoma (65). Moreover, deepHaem predicted that rs17713054-A would resulted in induced binding of CEBPB in A549 cells and IMR-90 (29) . This study found that rs17713054is an active enhancer of LZTFL1 in lungs and associated with increased risk of COVID-19 and is not in an active enhancer in immune cells, where CCR9 is expressed.…”
Section: Introductionmentioning
confidence: 65%
“…A recent study by Oxford University scientists was published in Nature genetic ( Nat Genet 53, 1606-1615 (2021). https://doi.org/10.1038/s41588-021-00955-3) showed that leucine zipper transcription factorlike 1(LZTFL1), as a candidate causal gene and its enhancer the rs17713054 A risk allele was signi cantly responsible for the twofold increased risk of respiratory failure from COVID-19 associated with 3p21.31 (29). LZTFL1 is widely expressed in pulmonary epithelial cells, including ciliated epithelial cells, which have been identi ed as one of the main cellular targets for SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Oxford University scientists was published in Nature genetic ( Nat Genet 53, 1606-1615 (2021). https://doi.org/10.1038/s41588-021-00955-3) showed that leucine zipper transcription factor-like 1(LZTFL1), as a candidate causal gene and its enhancer the rs17713054 A risk allele was signi cantly responsible for the twofold increased risk of respiratory failure from COVID-19 associated with 3p21.31 (29). LZTFL1 is widely expressed in pulmonary epithelial cells, including ciliated epithelial cells, which have been identi ed as one of the main cellular targets for SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…The 3p21.31-related risk is most likely caused by pulmonary epithelial cells undergoing EMT, rather than immune cells, according to this study. LZTFL1 could be a therapeutic target because the 3p21.31 effect is conferred by a gain-of-function (29). LZTFL1 variants that induce risk of severe COVID-19 disease is not found in immune cells as in this study they rst examined open chromatin from 24 diverse immune cell populations (including T, B, natural killer and dendritic cells) in resting and stimulated states but did not identify any of the 28 severe COVID-19-associated variants of LZTFL1 at 3p21.31 in open chromatin making it unlikely that a cis-regulatory mechanism in these immune cell types is responsible for COVID-19 risk.…”
Section: Introductionmentioning
confidence: 99%